VULNERABILITY AS A LIMIT TO THE LEGAL AUTONOMY OF THE PATIENT? - BIOY, Xavier (MEDECINE LEGALE DROIT MEDICAL, 2025)
The links between autonomy and vulnerability, in the context of health and law, are complex because the protection of patients can be temporary or institutionalized for long time, but also sometimes both. On the one hand, the notion of vulnerability prevents the loss of autonomy (on the margins of civil protection), not to establish the lack of autonomy but to avoid it; on the other hand, the notion of vulnerability corrects the excessive effects of protective regimes by refining them and affirming their subsidiarity.